2020
DOI: 10.1111/ggi.13976
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal value of the Geriatric Nutritional Risk Index to screen older patients with malnutrition risk: A study at a university hospital in Japan

Abstract: Aim The Geriatric Nutritional Risk Index (GNRI) can predict nutritional risk. However, just a few studies have validated the optimal cut‐off value of GNRI for nutrition screening in older patients. Hence, this study aimed to determine the optimal value of GNRI to screen the risk of malnutrition among older patients. Methods This retrospective cross‐sectional study was carried out with 5867 consecutive older adult patients who were admitted to an academic hospital in Japan. Receiver operating characteristic cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…They reported a GNRI cutoff value < 91.2 as the most accurate for identifying malnourished patients, according to the MIS. Another study at a university hospital reported an optimal cutoff GNRI value of < 96 for nutritional screening among older patients [19]. The suggested GNRI values for identifying malnutrition may differ between various clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a GNRI cutoff value < 91.2 as the most accurate for identifying malnourished patients, according to the MIS. Another study at a university hospital reported an optimal cutoff GNRI value of < 96 for nutritional screening among older patients [19]. The suggested GNRI values for identifying malnutrition may differ between various clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the GNRI cutoff value for mortality prediction, we calculated Harrell's C-index of GNRI in the multivariate Cox regression model (Model 3) [19]. The highest value of C-index was identified as the cutoff value of GNRI for all-cause mortality in this population.…”
Section: Discussionmentioning
confidence: 99%